Time zone chart of the world - United States. Hydrographic Office (Washington, D.C. : United States. Hydrographic Office, 1927)
Annotated by Charles A. Lindbergh showing New York to Paris flight route and note in corner. "No. 5192." Includes "Explanation". "Used for laying out route for New York to Paris flight, San Diego, California, 1927, C.A.L." -- handwritten by Charles A. Lindbergh in the lower right corner. Indexed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography. Annotated to read: “Used for laying out route for New York to Paris flight, San Diego, California, 1927 C.A.L.” While Ryan Airlines, Inc. of San Diego was constructing Lindbergh’s plane, Spirit of St. Louis, he was busy obtaining charts and plotting his course (Lindbergh 1927, p. 201-202). In order to obtain charts of the North Atlantic Ocean, Lindbergh had to fly to San Pedro, California. In his book The Spirit of St. Louis (1953), Lindbergh describes purchasing a number of charts at a store in San Pedro including this Time zone chart of the world: “The salesman pulls out two oblong sheets. They're Mercator's projections and –yes, I'm in luck—they extend inland far enough to include New York and Paris. Then, like stumbling over a nugget of gold, I see a gnomonic projection covering them both…Rummaging around still farther, I locate a time-zone chart of the world, a chart of magnetic variation, and others showing prevailing winds over the Atlantic for April, May, and June. I buy them all” (Lindbergh 1953, p. 93). Lindbergh does not give us the exact number of charts he bought at the store in San Pedro. However, it appears that he purchased the two "Mercator's projections" charts upon which he plotted his intended course in 100 mile segments. These two charts, now at the Missouri Historical Society in St. Louis, were actually taken on the flight. The three charts listed in this work and preserved in the AGS Library also appear to have been purchased in San Pedro. The AGS Library also has a fragment cut from the northeastern sheet of the charts taken on the flight and a Great circle sailing chart of the North Pacific ...